Implementasi Pembelajaran Baca Tulis Al-Qur’an Pada Anak Usia Dini - Nurjanah, Tri Siti Soleha; Syahrul (Al-Khidmah : Jurnal Pengabdian dan Pendampingan Masyarakat, 2024)
The Qur'an is the word of Allah that was revealed to the Prophet Muhammad SAW, through the angel Gabriel, as a miracle and mercy for the universe. It contains instructions, guidelines and lessons for those who believe in it and practice it. The Qur'an is so noble that just reading it is considered worship, especially by contemplating the meaning stored in it. Reading the Qur'an indeed provides many rewards and great advantages for a person. However, when reading the Koran, we cannot just read it like that. Every word in the Koran has a meaning, and if you read it incorrectly, it can change the meaning of the word. Introduction to learning to read and write the Qur’an is one of the obligations that must be given to young children as part of the Muslim community. The Al-Qur'an as the holy book of Muslims acts as a source of law, the basis of science and as a benchmark in shaping the behavior of early childhood. through learning the basics of the Al-Qur'an, such as reading and writing it, children become acquainted with the good values ​​contained in the Al-Qur'an. The formation of religious character is through learning the Koran, one of which is being able to read and write it. Qur'anic religious and personal character is needed in forming a civilized nation.